PENANGANAN KESULITAN BELAJAR ANAK DENGAN ADHD - Siti Asiya (Universitas Karimun Prodi S1 Pendidikan Luar Biasa, 2023)
Every child has the same right to get learning, but not all children can be treated the same as children with ADHD. Behavior that is different from children in general makes children with ADHD need a different way to learn. There are several Psychological Service Centers implementing various approaches which are a series of activities or programs to improve the learning abilities of children with ADHD. Some of these approaches are (1) collaboration between parents and therapists, (2) training children to sit independently, (3) sports, (4) learning activities (academic), (5) behavior modification, (6) use of APE, ( 7) the use of rewards, (8) EFT (emotional freedom technique) therapy, and (9) motivation. There are so many choices of approaches offered to improve learning abilities for adhd. Parents and teachers just have to choose and apply the appropriate approach if applied to children with ADHD who have barriers in accepting learning. Because a suitable approach certainly makes it easier for children with ADHD to receive learning.